Teknik Assosiasi Mining Menggunakan Algoritma Apriori Pada Penyebaran Covid-19 Di Kabupaten Kaur - Alber Uci Saputra; Erwin Dwika Putra; M. Husni Rifqo (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2022)
Covid-19 is a virus that appeared at the end of 2019, the process of spreading the virus was also considered very fast until it entered the country of Indonesia. Covid-19 is also considered as a factor inhibiting the development of a country to an area. In the kaur district area of Bengkulu City, the spread of covid-19 causes economic growth to be hampered due to established rule factors ranging from not being able to do activities related to others directly. The problem also occurs at the rate of spread of covid-19 in Kaur Regency due to the factors of the community who do not know how many people are infected with covid-19. Therefore, by applying classification, it is the right way to find out the rate of spread of COVID-19. One of them is to apply mining association techniques using a priori algorithms to see the rate of spread of COVID-19 in Bengkulu City, Kaur Regency. To find out the rate of spread of covid-19, the attributes are used to predict the rate of spread of COVID-19. Later the prediction system that will be made for the spread of covid-19 is intended for between villages in Kaur regency by using date and village name attribute data so that from this study resulted in a priori algorithm successfully applied to the analysis of the spread of covid-19 in Kaur regency, by obtaining the most frequently appeared village results are dapo coral villages with a percentage weight of 84.21%. A priori algorithm is a classification model to get a good spread analysis in conducting data mining classification.